2015
DOI: 10.5812/ircmj.20281
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Graft Survival After Diagnosis of Post-kidney Transplant Malignancy: Using Cox Proportional Hazard Model

Abstract: Background:All recipients of kidney transplantation, especially those with posttransplant malignancy, are at risk of long-term graft failure.Objectives:The purpose of our study was to evaluate the risk factors associated with graft survival after diagnosis of malignancy.Patients and Methods:To reach this purpose, we conducted a historical cohort study in Iran and 266 cases with posttransplant malignancy were followed up from diagnosis of malignancy until long-term graft loss or the date of last visit. These pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The observed multicollinear relationship between age, DPTM occurrence, and graft survival has not previously been highlighted. Previous studies have identified specific cancer types, treatment modalities, and response to treatment as significant predictors of graft survival following DPTM diagnosis [49,50] However, the optimal management strategies for balancing cancer control and graft preservation remain areas of ongoing investigation, thus necessitating personalized approaches tailored to individual patient characteristics and treatment responses.…”
Section: Discussionmentioning
confidence: 99%
“…The observed multicollinear relationship between age, DPTM occurrence, and graft survival has not previously been highlighted. Previous studies have identified specific cancer types, treatment modalities, and response to treatment as significant predictors of graft survival following DPTM diagnosis [49,50] However, the optimal management strategies for balancing cancer control and graft preservation remain areas of ongoing investigation, thus necessitating personalized approaches tailored to individual patient characteristics and treatment responses.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, a large volume of medical and statistical research has been performed to identify the effective factors for the survival rate of renal graft throughout the world (15,16,18,22,25,26,28,33). In these studies, the data analysts generally applied the usual statistical models, such as Cox proportional hazards or other well-known parametric or semi-parametric survival models.…”
Section: Archive Of Sidmentioning
confidence: 99%
“…Foroushani et al, in 2015, assessed long-term kidney graft failure and evaluated the risk factors of graft survival of patients who had malignancy after transplantation (15). Ghanei et al, in a historical cohort study, evaluated shortand long-term graft survival of patients who underwent kidney transplants from living or deceased donors.…”
Section: Introductionmentioning
confidence: 99%